Alterations of GABA and glutamate–glutamine levels in premenstrual dysphoric disorder: A 3T proton magnetic resonance spectroscopy study - Liu, Bo; Wang, Guangbin; Gao, Dongmei; Gao, Fei; Zhao, Bin; Qiao, Mingqi; Yang, Huan; Yu, Yanhong; Ren, Fuxin; Yang, Ping; Chen, Weibo; Rae, Caroline D. (Psychiatry research. Neuroimaging, 2015)
Increasing evidence has suggested that the GABAergic neurotransmitter system is involved in the pathogenesis of premenstrual dysphoric disorder (PMDD). We used proton magnetic resonance spectroscopy (1H MRS) to investigate whether PMDD is associated with alterations in brain GABA levels. Levels of glutamate–glutamine (Glx) were also explored. Participants comprised 22 women with PMDD and 22 age-matched healthy controls who underwent 3T 1H MRS during the late luteal phase of the menstrual cycle. GABA+ and Glx levels were quantified in the anterior cingulate cortex/medial prefrontal cortex (ACC/mPFC) and the left basal ganglia (ltBG). Water-scaled GABA+ concentrations and GABA+/tCr ratios were significantly lower in both the ACC/mPFC and ltBG regions of PMDD women than in healthy controls. Glx/tCr ratios were significantly higher in the ACC/mPFC region of PMDD women than healthy controls. Our preliminary findings provide the first report of abnormal levels of GABA+ and Glx in mood-related brain regions of women with PMDD, indicating that dysregulation of the amino acid neurotransmitter system may be an important neurobiological mechanism in the pathogenesis of PMDD. •This study examines GABA+ and Glx levels in PMDD.•PMDD women have decreased GABA+ levels in ACC/mPFC and ltBG.•PMDD women have increased Glx levels in ACC/mPFC.•Dysregulation of GABAergic/glutamatergic system may be important in PMDD.